Intravenous iron does Not augment the hemoglobin mass response to simulated hypoxia - Garvican-Lewis, L. A.; Vuong, V. L.; Govus, A. D.; Peeling, P.; Jung, G.; nemeth, E.; Hughes, D.; Lovell, G.; Eichner, D.; Gore, C. J. (Medicine & Science in Sports & Exercise, 2018)
Purpose Iron is integral for erythropoietic adaptation to hypoxia, yet the importance of supplementary iron compared with existing stores is poorly understood. The aim of the present study was to compare the magnitude of the hemoglobin mass (Hbmass) in response to altitude in athletes with intravenous (IV), oral, or placebo iron supplementation.